2015
DOI: 10.1002/alr.21615
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities of asthma and the unified airway

Abstract: Otolaryngologists should be aware of the unified airway in order to most effectively treat their patients with AR. Knowledge of the close relationships between asthma and AR will help prevent progression of disease, identify early asthma, and improve the outcomes and quality of life for our patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 65 publications
2
28
0
1
Order By: Relevance
“…There is a consecutive process in the progression of AR into asthma, as previously demonstrated by a long-term follow-up study (22). This has also been confirmed through a retrospectively study (23,24). The present results showed that the mean duration of AR was longer than asthma in the AR with asthma group, although certain patients reported that asthma was diagnosed earlier than AR.…”
Section: Discussionsupporting
confidence: 88%
“…There is a consecutive process in the progression of AR into asthma, as previously demonstrated by a long-term follow-up study (22). This has also been confirmed through a retrospectively study (23,24). The present results showed that the mean duration of AR was longer than asthma in the AR with asthma group, although certain patients reported that asthma was diagnosed earlier than AR.…”
Section: Discussionsupporting
confidence: 88%
“…In the unified airway model, patients with lower‐tract disease have an increased incidence of upper airway involvement. Similar histopathologic findings, including mucosa remodeling, have been noted in both asthma and CRS . Rhinosinusitis is more prevalent in patients with asthma than in those without asthma .…”
supporting
confidence: 68%
“…As highlighted by the united airways concept, there are important pathological links between rhinitis and asthma, and this fact is largely independent of the inflammatory endotype . Therefore, the bronchospasm‐inducing potential of NACs both in asthmatic and nonasthmatic rhinitis patients warrants an investigation.…”
Section: Discussionmentioning
confidence: 99%